Florida Consumer Perception of the Fresh from Florida Campaign on Horticulture Plants - Hayk Khachatryan; Alicia Rihn (EDIS)
Consumer demand for local products is increasing all the time because of perceptions of superior quality and the idea that local products benefit personal health, the local community, and the environment. Many states have publicly funded marketing programs to promote the consumption of local products. In a new development in Florida, the Department of Agriculture and Consumer Services (FDACS) has partnered with the Florida Nursery, Growers, and Landscape Association to include horticulture plants in the state’s Fresh from Florida campaign for the first time. This 3-page report provides an overview of Florida consumer perceptions of the new Fresh from Florida campaign for horticultural plants. Growers, wholesalers, marketers, and retailers can use the tips inside to understand consumer perceptions and discover how best to use the promotional materials of the new program to reach consumers, reduce economic risks, and improve their returns on investment. Written by Hayk Khachatryan and Alicia Rihn, and published by the Food and Resource Economics Department, December 2015.